John Dewey’s pedagogy and its relevance in the 1st cycle of basic education - Ferreira, Jessica; Cardoso, Ana Paula; Rocha, João (Millenium - Journal of Education, Technologies, and Health, 2020)
Introduction: John Dewey is one of the most renowned pedagogues of the 20th century, defending innovation and experimentation in the teaching-learning process, and so it is important to reflect on these ideals and their relationship with pedagogy in the 1st Cycle of Basic Education (CEB). Objectives: To know the perspective of teachers of the 1st CEB about Dewey’s pedagogical ideals; understand if they employ this pedagogy and perceive what the main barriers to its implementation are and suggestions to overcome them. Methods: Cross-sectional, descriptive, and comparative research, using a questionnaire. The sample consisted of 96 teachers (84.4% female), aged between 25 and 61 years (M = 48.30; SD = 6.53), from the 1st CEB from three school groupings of the municipality of Viseu (Portugal). Results: Most teachers admitted that 1st CEB teaching is based on Dewey's pedagogical ideals. However, they consider that there are factors, like the number of students per class or the extension of the programs, that hinder their pedagogical action and they presented suggestions to overcome them. Conclusion: Teachers have a favourable perspective on the principles of Dewey pedagogy, revealing that their pedagogical action is framed by these principles. Nevertheless, there are serious constraints that hinder a consistent action based on these ideals, that only an educational reform can help to overcome.